Engineering Rhizosphere Hydraulics: Pathways to Improve Plant Adaptation to Drought - Ahmed, M.A. (2020)
Rhizoligand treatment quickly and uniformly rewetted the rhizosphere of maize and lupine. Interestingly, rhizoligands also reduced transpiration during drying–wetting cycles. Our hypothesis is that the reduction in transpiration was triggered by the interaction between rhizoligand and mucilage exuded by roots. This hypothesis is supported by the fact that rhizoligand reduced the maximum swelling of mucilage, increased its viscosity, and decreased the hydraulic conductivity of soil–mucilage mixtures. The reduced conductivity of the rhizosphere induced a moderate stress to the plants, reducing transpiration. Rhizoligands increase the rhizosphere wetting kinetics and decrease the maximum swelling of mucilage. As a consequence, root rehydration following irrigation is faster, a larger volume of water is available to the plant, and this water is used more slowly. This slower water consumption would allow the plant to stay turgid during a prolonged drying period. We propose that by managing the hydraulic properties of the rhizosphere, we can improve plants' adaptation to drought.